Efficacy of Three Different Prophylactic Treatments for Postoperative Nausea and Vomiting after Vitrectomy: A Randomized Clinical Trial - Reibaldi, Michele (J Clin Med, 2019)
Postoperative nausea and vomiting (PONV) after vitreoretinal surgery may potentially be associated with severe complications, such as suprachoroidal hemorrhage. The purpose of the present multicenter clinical trial (NCT02386059) was to assess the efficacy of three different prophylactic treatments for PONV after vitrectomy under local anesthesia. Patients undergoing primary vitrectomy were randomized to the control arm or to one of the treatment arms (4 mg ondansetron, 4 mg dexamethasone, combination of the two drugs). The primary outcome measure was the proportion of complete response (no nausea, no vomiting, no retching, and no use of antiemetic rescue medication) during 24 h after vitrectomy. Secondary outcomes included the severity standardized score of PONV, postoperative pain standardized score, and rate of ocular and non-ocular adverse events. Baseline demographics of the 1287 patients were comparable between the four arms. The combined therapy group showed a statistically significant lower incidence of PONV compared to the placebo and monotherapy (p < 0.001). PONV severity was also reduced in the combination group compared to the others (p < 0.001). Postoperative pain scores and adverse events were comparable among the four groups. Combined therapy with dexamethasone and ondansetron was the most effective treatment for reducing the incidence and severity of PONV in patients undergoing vitrectomy under local anesthesia.